The importance of cost-benefit analysis: a response - David Nicol; Michael Coen (Association for Learning Technology, 2003)
The critique by Draper raises some interesting points that we did not have space to discuss in our published paper. As he points out, taking a purely quantitative approach to the evaluation of ICT investments in teaching and learning is wholly inappropriate. However, in this transitional period, where ICT applications are new and the effects on operational processes within higher education institutions are unknown, it is not only qualitative issues that need to be investigated but also the potential changes to the scope and nature of the costs incurred by institutions. While the small-scale, and localized, introduction of ICT in teaching might only affect the time and effort of a few individual academics, large-scale deployment of the same methodology may require substantial institutional investment (for example, in network infrastructure, hardware, licenses, support staff). The CBA model encourages institutions to consider and record all the cost implications of their strategies, not in an attempt to quantify the outputs (benefits) of these new learning processes but to identify and quantify the inputs to these processes. These quantitative inputs can then be evaluated in the context of qualitative outputs.